2019
DOI: 10.1021/jacs.9b10354
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Chelation Chemistry for Actinium and Other +3 f-Elements, Am, Cm, and La

Abstract: A major chemical challenge facing implementation of 225 Ac in targeted alpha therapyan emerging technology that has potential for treatment of diseaseis identifying an 225 Ac chelator that is compatible with in vivo applications. It is unclear how to tailor a chelator for Ac binding because Ac coordination chemistry is poorly defined. Most Ac chemistry is inferred from radiochemical experiments carried out on microscopic scales. Of the few Ac compounds that have been characterized spectroscopically, succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 76 publications
5
49
0
Order By: Relevance
“…While the direct interactions between Ac 3+ and carbonate, selenite, or phosphate ions have never been probed under biorelevant conditions, our results indicate that Ac 3+ exhibits stronger interactions with softer oxygen donors. In line with our experimental results, recent density functional theory calculations 50 showed that replacing DOTA's carboxylate groups by phosphonate groups would impart enhanced stability for the Ac 3+ complex. However, the design of new actinium complexants should also take into account the selectivity against natural cations, a challenge for most small molecules.…”
Section: Lanmodulin Enables Facile Detection Of Radiometals Even At Ultra-trace Levelssupporting
confidence: 91%
“…While the direct interactions between Ac 3+ and carbonate, selenite, or phosphate ions have never been probed under biorelevant conditions, our results indicate that Ac 3+ exhibits stronger interactions with softer oxygen donors. In line with our experimental results, recent density functional theory calculations 50 showed that replacing DOTA's carboxylate groups by phosphonate groups would impart enhanced stability for the Ac 3+ complex. However, the design of new actinium complexants should also take into account the selectivity against natural cations, a challenge for most small molecules.…”
Section: Lanmodulin Enables Facile Detection Of Radiometals Even At Ultra-trace Levelssupporting
confidence: 91%
“…The prospect of such an elaborative study for radioactive An m+ cations as well, is expressed by the possible pharmaceutical applications of such kinetically inert complexes. The use of the tetramethylene phosphonic DOTA derivative, DOTP ( 1,4,7,10‐Tetraazacyclododecane‐1,4,7,10‐tetra(methylene phosphonic acid) ) complexes of 225 Ac 3+ and 227 Th 4+ , two possible alpha‐particle emitters therapeutic agents, was proposed previously [1f,4] . A similar coordination environment may also be relevant for future applications with 230 U – a possible alpha emitter suggested for targeted alpha‐therapy, [5] but one which lacks at the moment a proper chelate for safe application [6] .…”
Section: Methodsmentioning
confidence: 99%
“…Macropa (Figure b) is one example of a promising chelator that can quantitatively label Ac at submicromolar (<10 −6 m ) levels, and has recently been used as part of a novel PSMA‐targeting radiopharmaceutical (RPS‐074) . Several other chelators (bispa 2 , CHXoctapa, and DOTP) demonstrate high Ac binding affinity as well, though in vivo stability has not yet been evaluated. Some other chelators have limited success either due to binding affinity (TETA, TETPA, DOTPA) or in vivo stability (DOTMP, HEHA) .…”
Section: Figurementioning
confidence: 99%